تقويم إدارة نظام النقل بالسكك الحديدية في سورية - ديوب محمد عباس (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث إدارة نظام النقل السككي في سورية ودراسته دراسة تحليلية واقعية بهدف التعرف على ايجابيات هذا النظام وسلبياته, ونقاط الضعف فيه, وتسليط الضوء عليها ووضع المقترحات لمعالجتها. تضمن البحث مجموعة من الجوانب وأهمها: - خصائص النقل السككي. - العناصر الأساسية للنقل السككي. - رفع كفاءة النقل بالسكك الحديدية. - معايير المقارنة بين السكك الحديدية وأنواع النقل الأخرى. - واقع النقل السككي في سورية. وبعد الدراسة والتحليل تم التوصل إلى مجموعة من النتائج وأهمها: - عدم الاهتمام الكافي بالنقل السككي. - تراجع تطوير النقل السككي مقابل تطوير أكبر في أنواع النقل الأخرى وخاصة السيارات. - عدم تلاؤم نظام النقل السككي مع حاجات القطر للنقل. - ضعف الطلب على النقل السككي وخاصة نقل الركاب. This research presents a an analytical study of the administration of railway transport system in Syria in order to determine its positive and negative points and suggest ways of improvement. The research includes the following: - Railway transport characteristics. - Railway transport basic elements. - Increasing the efficiency of Railway transport. - Comparing standards between railway and other transport means. - The existing of Railway transport in Syria. Research results: - No sufficient interest in railway transport. - A decrease in the development of railway compared with the increase in other kinds of transport, especially the cars. - The railway system in not suitable to the transport needs in the country. - Weak demand on Railway transport, especially in the passenger field.